Informal Payments in the Health Care System - Research, Media and Policy - Răzvan Cherecheş; Marius Ungureanu; Ioana Rus; Cătălin Baba (Transylvanian Review of Administrative Sciences, 2011)
Informal payments in the health system refer to any payment made outside the legal funding framework. The existence of the phenomenon in Central and Eastern European countries relates to the characteristics of the health systems in the communist period. The analysis is based on three types of data: a set of data gathered from literature review; a second set of data gathered from online media; and a third set of data collected from legislative and public policy. The analysis was pursued using the key words such as informal payment, under-the-table payment, out-of-pocket payment, envelope payment, healthcare corruption, under-the-counter payment. As reflected in the media reports and even publicly recognized by the officials of the Ministry of Health, informal payments are a serious problem of the Romanian healthcare system. Nevertheless, the studies pursued by local researchers are inconsistent with the actual magnitude of the problem. Besides that, there is a serious gap between the findings in this area and the policies intended to reduce the phenomenon.